Endoscopic characterization of colorectal neoplasia with different published classifications: comparative study involving CONECCT classification - Bonniaud, Paul; Jacques, Jérémie; Lambin, Thomas; Gonzalez, Jean-Michel; Dray, Xavier; Coron, Emmanuel; Leblanc, Sarah; Chevaux, Jean-Baptiste; Léger-Nguyen, Florence; Hamel, Benjamin; Lienhart, Isabelle; Rivory, Jérôme; Ponchon, Thierry; Saurin, Jean-Christophe; Monzy, Frédéric; Legros, Romain; Lépilliez, Vincent; Subtil, Fabien; Barret, Maximilien; Pioche, Mathieu (Endoscopy International Open, 2022)
Background and study aims The aim of this study was to validate the COlorectal NEoplasia Classification to Choose the Treatment (CONECCT) classification that groups all published criteria (including covert signs of carcinoma) in a single table.Patients and methods For this multicenter comparative study an expert endoscopist created an image library (n = 206 lesions; from hyperplastic to deep invasive cancers) with at least white light Imaging and chromoendoscopy images (virtual ± dye based). Lesions were resected/biopsied to assess histology. Participants characterized lesions using the Paris, Laterally Spreading Tumours, Kudo, Sano, NBI International Colorectal Endoscopic Classification (NICE), Workgroup serrAted polypS and Polyposis (WASP), and CONECCT classifications, and assessed the quality of images on a web-based platform. Krippendorff alpha and Cohen’s Kappa were used to assess interobserver and intra-observer agreement, respectively. Answers were cross-referenced with histology.Results Eleven experts, 19 non-experts, and 10 gastroenterology fellows participated. The CONECCT classification had a higher interobserver agreement (Krippendorff alpha = 0.738) than for all the other classifications and increased with expertise and with quality of pictures. CONECCT classification had a higher intra-observer agreement than all other existing classifications except WASP (only describing Sessile Serrated Adenoma Polyp). Specificity of CONECCT IIA (89.2, 95 % CI [80.4;94.9]) to diagnose adenomas was higher than the NICE2 category (71.1, 95 % CI [60.1;80.5]). The sensitivity of Kudo Vi, Sano IIIa, NICE 2 and CONECCT IIC to detect adenocarcinoma were statistically different (P < 0.001): the highest sensitivities were for NICE 2 (84.2 %) and CONECCT IIC (78.9 %), and the lowest for Kudo Vi (31.6 %).Conclusions The CONECCT classification currently offers the best interobserver and intra-observer agreement, including between experts and non-experts. CONECCT IIA is the best classification for excluding presence of adenocarcinoma in a colorectal lesion and CONECCT IIC offers the better compromise for diagnosing superficial adenocarcinoma.